The Antibiotics Used in Livestock and Their Impact on Resistance in Enterococcus faecium and Enterococcus hirae on Farms in Gabon - Désiré Otsaghe Ekore; Richard Onanga; Pierre Phillipe Mbehang Nguema; Chloé Lozano; Brice Serge Kumulungui (Antibiotics, 2022)
The emergence of antibiotic resistance is a major concern around the world. The objective of this study was to investigate the antibiotics used in livestock and their impact on resistance in Enterococcus faecium and Enterococcus hirae on farms in Gabon. A structured questionnaire was used to collect information on the farms. Samples were collected from farms (n = 20) tested for Enterococcus by culture and isolation and were identified using a polymerase chain reaction (PCR) and sequencing. Antibiotic susceptibility was determined by the disc diffusion method on Mueller Hinton agar. The 20 farms included laying hens (6), swine (6), sheep (4) and cattle farms (4). Tetracycline was the most used antibiotic family (91%) and the most used prophylactic method (47%) for the treatment of animals. A total of 555 samples were collected and 515 (93%) Enterococcus spp. isolates of the genus were obtained. The prevalence of E. faecium and E. hirae were 10% and 8%, respectively. The isolates from E. faecium and E. hirae we found were related to clinical and human isolates in the NCBI database. E. faecium and E. hirae isolates showed a high resistance to tetracycline (69% and 65%) and rifampicin (39% and 56%). The tet(M) gene was detected in 65 tetracycline-resistant isolates with a large majority in hens (78% (21/27) and 86% (12/14) in E. faecium and E. hirae, respectively). The consumption of antibiotics favours the emergence of antibiotic resistance in animals in Gabon.